Current and emerging technologies for the timely screening and diagnosis of neonatal jaundice. (4th July 2022) - Thomas, Mercy; Greaves, Ronda F.; Tingay, David G.; Loh, Tze Ping; Ignjatovic, Vera; Newall, Fiona; Oeum, Michelle; Tran, Mai Thi Chi; Rajapaksa, Anushi E.
Abstract: Neonatal jaundice is one of the most common clinical conditions affecting newborns. For most newborns, jaundice is harmless, however, a proportion of newborns develops severe neonatal jaundice requiring therapeutic interventions, accentuating the need to have reliable and accurate screening tools for timely recognition across different health settings. The gold standard method in diagnosing jaundice involves a blood test and requires specialized hospital-based laboratory instruments. Despite technological advancements in point-of-care laboratory medicine, there is limited accessibility of the specialized devices and sample stability in geographically remote areas. Lack of suitable testing options leads to delays in timely diagnosis and treatment of clinically significant jaundice in developed and developing countries alike. There has been an ever-increasing need for a low-cost, simple to use screening technology to improve timely diagnosis and management of neonatal jaundice. Consequently, several point-of-care (POC) devices have been developed to address this concern. This paper aims to review the literature, focusing on emerging technologies in the screening and diagnosing of neonatal jaundice. We report on the challenges associated with the existing screening tools, followed by an overview of emerging sensors currently in pre-clinical development and the emerging POC devices in clinical trials to advance the screening of neonatal jaundice. The benefits offered by emerging POC devices include their ease of use, low cost, and the accessibility of rapid response test results. However, further clinical trials are required to overcome the current limitations of the emerging POC's before their implementation in clinical settings. Hence, the need for a simple to use, low-cost POC jaundice detection technology for newborns remains an unsolved challenge globally.